HUMAN RIGHTS VIOLATIONS AGAINST OIL PALM PLANTATION WORKERS IN WEST KALIMANTAN REGION - Abdul Ghani Naufal Rabbani; Arthania Callista Bunga Julianto; Ni Komang Ariska Argun Gayatri; Putu Ananda Mustika Karina Padang Galuh (President University, 2024)
Indonesia, a leading palm oil producer, faces a dilemma between the palm oil sector's positive economic contribution and its negative impact on labor rights. Despite creating jobs and economic growth, the sector is often associated with rights violations such as corruption, job insecurity, low wages, forced labor, occupational safety, child labor, and social security. Case studies in West Kalimantan and Central Sulawesi highlight the issues that need to be addressed to strike a balance between economic development and human rights protection in Indonesia's palm oil sector.Keywords: Human Rights, Plantation Labor, Oil Palm, Worker